Prenatal and perinatal history in Kabuki Syndrome. Issue 1 (26th October 2019) - Rosenberg, Chen E.; Daly, Tara; Hung, Christina; Hsueh, Irene; Lindsley, Andrew W.; Bodamer, Olaf
Abstract: Kabuki syndrome (KS) is a disorder of epigenetic dysregulation due to heterozygous mutations in KMT2D or KDM6A, genes encoding a lysine‐specific methyltransferase or demethylase, respectively. The phenotype is highly variable, including congenital cardiac and renal anomalies, developmental delay, hypotonia, failure to thrive, short stature, and immune dysfunction. All affected individuals have characteristic facial features. As KS natural history has not been fully delineated, limited information exists on its prenatal and perinatal history. Two tertiary centers collected retrospective data from individuals with KS ( N = 49) using a questionnaire followed by review of medical records. Data from 49 individuals (age range: 7 months–33 years; 37% male; 36 with KMT2D mutations, 2 with KDM6A mutations, and 11 diagnosed clinically) were examined. Polyhydramnios affected 16 of 39 (41%) pregnancies. Abnormal quad screens in four out of nine (44%) pregnancies and reduced placental weights also complicated KS pregnancies. These data comprise the first large dataset on prenatal and perinatal history in individuals with confirmed (genetically or clinically) KS. Over a third of pregnancies were complicated by polyhydramnios, possibly secondary to abnormal craniofacial structures and functional impairment of swallowing. The differential diagnosis for polyhydramnios in the absence of intrauterine growth retardation should include KS.